Global health education program: experience of a multidisciplinary curriculum at the school of medicine in Rouen, France (One Health & Risk Management, 2021)
Introduction. The One Health (OH) approach is based on the notion that human, animal, and environmental health are intimately connected and mutually dependent. Consequently, advocates of this movement describe the need for transdisciplinary approach when tackling complex global health (GH) issues with high societal values.The interest in GH as an academic discipline has increased in the last decade. Global health, including OH, are increasingly taught in health training institutions.The Rouen School of Medicine is one of the first to offer a GH curriculum in France.The objective was to identify the characteristics and profile of students involved in GH curriculum.Material and methods. In 2019 and 2019, a cross-sectional study was conducted, including enrolled in the GH course: 3rd and 4th year in medicine, midwifes studies and pharmacy.Based on self-questionnaire, data collected were gender, age, motivations for health studies, investment in humanitarian actions and associations, opinions about the themes proposed for HG/OH teaching content and their future professional career.Results. A total of 422 students were included. In the group attended to GH cursus (GH+) and the control group (GH-), the sex ratio M: F was respectively 0.4 and 0.7, p=0.02.The students of the GH+ group were more likely to get involved in a humanitarian association (22.3% versus 6.7%, p
Keywords: global health; One Health; education; public health.